The Principle of third Party Protection in Financial Transaction Contracts: a legal juristic study - Nasser, Reham; Ziadat, Emad (Jordan Journal of Islamic Studies, 2023)
Contracts are considered as the most important tools that organize the financial relations between people. Each contract has an effect that is intended by contract parties, and commitments of each of the contract parties. Negative effects of contracts sometimes extend to a third party who did not intend to be part of the contract, therefore, they should not be held responsible or negatively affected by contract consequences, on the contrary, a third party should be protected from such effects, with the rights of contract parties be preserved. This research explains the concept of principle of third party protection, its elements, conditions and tools. The research has reached a number of conclusions, the most important amongst which are: the principle of third party protection prevents harm that could negatively affect a third party, this principle is built on consideration of elements amongst which are: the relation that obligates the protection of third party, and the harm that could affect others as a result of the contract, with the condition of good intention of third party. Islamic jurisprudence offers such a protection through variety of tools: the correction of invalid contract, ending the contract, suspension of contract on the permission of others, deleting the contract, prevention of ex post effect of invalidation and dissolution.